To Establish the Relationship between Proton Pump Inhibitors (PPIS) and Acute Interstitial Nephritis (AIN). Study Protocol - Bite Bapurao; Swanand Pathak; Ranjit Sidram Ambad (Journal of Pharmacy and Bioallied Sciences)
In India, utilization of PPI varies from 45 to 85%. PPIs were used in 82.96% of patients with chronic kidney disease. However, nowadays several case reports are suggesting PPI that induces AIN. The exact rate of this rare adverse event is difficult to estimate because many patients are taking multiple medications, which also make it difficult to establish a causal relation between AIN and PPI. Early detection of AIN and immediate discontinuation of the culprit drug may prevent the progress of AIN to the end stage of chronic kidney disease. So we planned a study to establish the relationship between PPI and AIN, if any.